Caesium −Methyl Ammonium Mixed-Cation Lead Iodide Perovskite Crystals: Analysis and Application for Perovskite Solar Cells. (10th December 2017) - Murugadoss, Govindhasamy; Thangamuthu, Rangasamy; Vijayaraghavan, Saranyan; Kanda, Hiroyuki; Ito, Seigo
Abstract: The present work addresses two important aspects; (i) crystalline formation of perovskites by fast powder production method (FPP) in large scale and its corresponding analysis and (ii) fabrication of mixed cation perovskite solar cells (PSC) by conventional one step method using inorganic copper (I) thiocyanate (CuSCN) as hole transport material (HTM). In this work, we investigate a stable and stoichiometrically variable Cs content in powdered MAPbI3 perovskites. For the first time, distinct morphologies like porous sheets, nanorods and nanowires, tightly bonded grains and fibre structures are collectively observed for the various concentrations of the Cs mixed with MAPbI3 by the FPP method, which finds applications in optoelectronic, energy and memory devices. In place of using expensive organic HTM, in this study, CuSCN is utilized as HTMs due to their cost and humidity resistance for the application to solar cells. The highest efficiency so far attained using CuSCN HTM in Csx MA1-x PbI3 composite PSC is being discussed.